PENGARUH CITRA, KUALITAS LAYANAN DAN KEPUASAN TERHADAP LOYALITAS PASIEN DI POLIKLINIK EKSEKUTIF RUMAH SAKIT DAERAH dr. SOEBANDI KABUPATEN JEMBER - Hidajahningtyas, Nurullah; Sularso, R. Andi; Suroso, Imam (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2013)
The studyaimedto examine the effect of brand image of dr Soebandi executive polyclinic, service quality and satisfaction to patient loyalty. There were six hypotheses were tested with path analysis using partial least squares instrument. Data were collected using a questionnaire. The results showed that first, second, third, and five hypotheses were received. Brand image influenced service quality and patient satisfaction. Analysis of direct and indirect effects indicated that the quality of service and patient satisfaction were intervening variables in the relationship with the brand image of an executive polyclinic to patient loyalty. Another hypothesis were rejected. Service quality andsatisfaction were an important mediator in the relationship between brand image and loyalty. These findings implied that the quality and satisfaction wereintervening variables to patient loyalty. Brand image played an important role in changing service quality and patient satisfaction. It would lead to better patient loyalty are higher as well. Key words: brand image, service quality, satisfaction, patient loyalty